Rancang Bangun Alat Uji Termolelektrik Portabel Dan Analisis Rangkaian Termoelektrik - Nuzul Hesty Pranita; Kiki Azura; Abrar Ismardi; Tri Ayodha Ajiwiguna; Ismudiati Puri Handayani (eProceedings of Engineering, 2015)
Abstract—Computer has been part of our daily life. In order to work properly and to avoid over heating which might damage the machine, it required a cooling system which effectively distribute heat from the electronic devices into surrounding environment. Generally, the cooling system only distributes the heat. The potential heat conversion into electricity in computer has not been studied intensively. In this study, we implement a thermoelectric generator module which converts heat into electicity in combination with hybrid cooling system on CPU processor, a main crucial part in computer system which produces a lot of heat and its work is very temperature dependent. We used a thermoelectric module TEG241-1.0-12 which can generate electricity up to 12.1 volt at temperature difference of 110oC and Seebeck coefficient from 35 mV/οC up to 45 mV/οC. The available size of thermoelectric module is found to be matched with the CPU processor and the hybrid heat sink structure so that no structural adjustment is required. We used hybrid cooling system of PC Cooler Hybrid W120 which consists of an aluminium heat sink and water cooling with flow rate of 6.7 liters/minute. We found that a 2.5 V and 0.19 A (≈ 0.5 W) electricity can be generated when a thermoelectrics module is implemented in Intel Core i3- 2100 microprocessor. The observed different temperature between hot and cold sides of thermoelectric is 54 οC while the processor temperature is 80 oC. This study shows the potential implementation of thermoelectric for heat conversion into electricity on CPU processor without endangers the machine. Keywords—thermoelectrics; CPU processor; hybrid cooling;